Implementation Of Community-based Flood Disaster Prevention Through Disaster Alert Villages In South Tangerang - Banten - Muhamad Taslim; Muhammad Khoirul Anwar; Ahmad Jamil Pasaribu; Evi Satispi; Azhari Aziz Samudra (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
Floods are one of the natural disasters that often occur in Indonesia. This flood disaster can cause various losses, such as infrastructure damage, economic loss, and even loss of life. Flood disaster prevention needs to be carried out comprehensively and involve various parties, including the community. This prevention can be done in various ways, one of which is the Disaster Preparedness Village. The purpose of this study was to assess the implementation of a community-based flood disaster prevention program through the Disaster Alert Village in South Tangerang, Banten. The research was conducted using a qualitative approach, where data was collected by using a literature study, the data collected is then analyzed through three steps, namely first reducing the data, presenting the data, and drawing conclusions. The conclusion of the study shows that the implementation of the Disaster Preparedness Village in South Tangerang has been implemented in several areas in South Tangerang. The Flood Alert Village program includes various activities, such as disaster response simulation training, counseling on disaster preparedness, and the formation of a disaster task force. Disaster Alert Village increases community preparedness in facing flood disasters, so that it can reduce the negative impacts of flood disasters.